2012
DOI: 10.1002/app.38183
|View full text |Cite
|
Sign up to set email alerts
|

Development of water‐blown bio‐based thermoplastic polyurethane foams using bio‐derived chain extender

Abstract: Water-blown bio-based thermoplastic polyurethane (TPU) formulations were developed to fulfill the requirements of the reactive rotational molding/foaming process. They were prepared using synthetic and bio-based chain extenders. Foams were prepared by stirring polyether polyol (macrodiol), chain extender (diol), surfactant (silicone oil), chemical blowing agent (distilled water), catalyst, and diisocyanate. The concentration of chain extender, blowing agent, and surfactant were varied and their effects on foam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…The typical absorption band of the urethanic bond was observed as the -NH vibrational stretching between 3500 and 3200 cm -1 (Tsai et al 1998) and the characteristic stretching vibration of -C=O groups between 1750 and 1600 cm -1 . Three absorption bands were found; the first one was at ~1550 cm -1 and was due to-CN urethanic linkages (Rashmi et al 2013). The remaining wavelengths at 1620 and 1730 cm -1 were due to C=O stretching, suggesting a phase separation in the bio-material (Zhang et al 1998).…”
Section: Ft-ir Characterization Of Arundo Donax L Hydrolysis Residuementioning
confidence: 99%
“…The typical absorption band of the urethanic bond was observed as the -NH vibrational stretching between 3500 and 3200 cm -1 (Tsai et al 1998) and the characteristic stretching vibration of -C=O groups between 1750 and 1600 cm -1 . Three absorption bands were found; the first one was at ~1550 cm -1 and was due to-CN urethanic linkages (Rashmi et al 2013). The remaining wavelengths at 1620 and 1730 cm -1 were due to C=O stretching, suggesting a phase separation in the bio-material (Zhang et al 1998).…”
Section: Ft-ir Characterization Of Arundo Donax L Hydrolysis Residuementioning
confidence: 99%
“…Basically, TPUs are produced from petroleum-based raw materials, i.e., diisocyanates, polyols and chain extenders. However, it has been demonstrated that at least part of the conventional petroleum-based polyols can be replaced by renewable resourcesbased equivalent compounds such as vegetable oils [4][5][6][7], and now, a major part of bio-based raw mate-rials derived from plant oils and natural fats is dedicated to polyurethane industry [4,5]. However, most of the reported bio-based polyurethanes are chemically cross-linked networks (thermosets) [6][7][8][9], except for a very few reports on syntheses of thermoplastics using either methanolysis, metathesis or an ozonolysis pathway, which means some parts of the original triacylglycerol were not utilized [10,13], and for the very recent renewable-sourced thermoplastic polyurethanes Pearlthane ® ECO from Merquinsa [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the reported bio-based polyurethanes are chemically cross-linked networks (thermosets) [6][7][8][9], except for a very few reports on syntheses of thermoplastics using either methanolysis, metathesis or an ozonolysis pathway, which means some parts of the original triacylglycerol were not utilized [10,13], and for the very recent renewable-sourced thermoplastic polyurethanes Pearlthane ® ECO from Merquinsa [9]. The approach adopted in this paper aims at developing partially bio-based TPU formulations suitable for reactive rotational molding (RRM), as previously achieved for TPU foams [5]. To the best of our knowledge, the following report is the first to address this approach in the case of bulk TPUs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase of EG content can accelerate gel reaction which facilitates gelation and in turn shorten tack free time. Moreover, the enhancement of heat release caused by the exothermic reaction of EG and isocyanate is also probable to cause a decrease in tack free time [22].…”
Section: Resultsmentioning
confidence: 99%